The credibility of transnational NGOs when virtue is not enough - Gourevitch, Peter Alexis; Lake, David A. 1956-; Stein, Janice Gross (Cambridge University Press, 2012)
We rely on NGOs to monitor the ethical practices of governments and for-profit firms and to undertake many humanitarian tasks that public and private actors will not do. While we are critical of public and private sector failures, we do not reflect enough on the credibility of the NGOs which take their place. Can we be sure that products NGOs label as child-labor free are in fact so, that the coffee labeled as 'fair trade' is farmed in sustainable ways, or that the working conditions monitored by NGOs are safe and that the wages are reasonable? Can we know that humanitarian organizations are, in fact, using our donations to alleviate human suffering rather than pursuing other goals? This book explores the problems of establishing the credibility of NGO activities as they monitor working conditions, human rights and elections and provide finance through microcredit institutions, development aid and emergency assistance